Perencanaan Pembangunan Pariwisata di Daerah (Studi Pelaksanaan Program pada Dinas Pemuda Olahraga dan Pariwisata Kabupaten Pekalongan) - Susanto, Irwan (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2016)
Tourism development in rural area implemented to eradicate poverty and the gap between rural and urban areas. The purpose of this study is to identify tourism development program that carried out in the rulal area from perspective of destination development, marketing and institutional development. Program destination development still dominated by the construction of infrastructure, in which lack attention to the construction of the attractions, the development of marketing is still stuck at an annual routine which has not based on modern marketing model, program of institutional development has been growing a tourism area in society however it is still not effective because of limited quality and quantity in human resources, accessibility, lack of facilities and infrastructure and also budget. The development model recommended is a community-based tourism development which pay more attention to community participation, environmental sustainability and social culture.